The revival of Shi‘ism in Southeast Asia and its responses: comparative study on the opinions of scholars and Islamic authorities - Muhamad Shukri, Abdul Salam; Wahyono, Zubaidi; Shobaruddin, Dudin (EAI, 2021)
Islam in Southeast Asia (SEA) in general and in Malaysia, Indonesia and Brunei in particular, has been dominated by the ideology of Sunnism since it arrived in the region in the 11th century. However, since few decades ago, other theology especially Shi’ism started to grab the followers among the Sunni Muslim society in the region amidst the controversies arisen. This paper studies the influence of Shi'ism among the Sunni Muslims in SEA particularly in Malaysia, Indonesia and Brunei in order to know how Shi'ism spread and its responses from Muslims scholars as well as religious authorities in the region. By employing library research and observation, this research present the current development of Shi'ism in the region and portray the analytical study on the responses and the opinions of Muslim scholars as well as with the prominent figures of the religious authorities in Malaysia, Indonesia and Brunei. Among the important findings of the research is that Shi’ism managed to get footstep in the region after the Iran revolution in 70th through various methods, education mission, socio-cultural relation as well as ideological propagation. However, as a new ideology, Shi’ism has sparked diverse responses and created polemic among the Muslims society especially among the Muslim scholars and the Islamic authorities in the region due its sensitive issue ideologically, economically and politically